The Role of Village Government in Economic Empowerment of Local Fishermen : A Study in Mengkait Village, Riau Islands - Marco Marco; Ika Devy Pramudiana; Sapto Pramono (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
This study discusses the strategic role of the village government in economic empowerment of local fishermen in Mengkait Village, Anambas Islands, Riau Islands Province. With a descriptive qualitative approach, this study illustrates how village governments facilitate training, fishing gear assistance, and the establishment of economic institutions to improve the welfare of fishermen. The results of the study show that the role of the village government is quite effective, characterized by increasing the capacity of fishermen, the involvement of vulnerable groups, and the participatory involvement of the community in development planning. However, some challenges are still faced, such as dependence on aid and weak financial literacy. These findings show that empowerment carried out in a planned, participatory, and local potential-based manner is able to create significant economic changes in coastal villages. This research is expected to be a policy reference for the empowerment of fishing communities in other 3T regions in Indonesia.